2016
DOI: 10.11648/j.jhrm.20160403.12
|View full text |Cite
|
Sign up to set email alerts
|

Technostress and Its Management Techniques: A Literature Review

Abstract: Abstract:Our work life effectiveness and efficiency has increased tremendously with the help of technology. But at the same time, the use of technology has increased the stress at workplace. Technostress is causing a lot of physical as well as psychological problems among workers. This paper discusses various work stressors and suggests some techniques such as stress management programs, training programs, autonomy and social support, awareness and communication to deal with work stress related problems. Liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…Fatigue in the workplace is not only related to negative results, but only to organizations, but also includes individuals who express depression, feelings of failure, fatigue or loss of motivation [8], [9]. Many international organizations, such as the International Labour Organization and the World Health Organization, are concerned that the tension caused by the use of ICTs affects the health of employees [10] This study aimed to review and propose a model to understand existing technostress faced by academic society by combining various sources in the area of information technology.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue in the workplace is not only related to negative results, but only to organizations, but also includes individuals who express depression, feelings of failure, fatigue or loss of motivation [8], [9]. Many international organizations, such as the International Labour Organization and the World Health Organization, are concerned that the tension caused by the use of ICTs affects the health of employees [10] This study aimed to review and propose a model to understand existing technostress faced by academic society by combining various sources in the area of information technology.…”
Section: Introductionmentioning
confidence: 99%
“…While the usage of technology has offered productivity, efficiency, and flexibility, it has also exacerbated technostress problems in the workplace. Prior studies related to this phenomenon confirmed that technostress could become a significant factor in personal health problem, job dissatisfaction, work inefficiency, and ineffectiveness (Boonjing & Chanvarasuth, 2017;Durucu & Bayraktar, 2020;Hung et al, 2015;Mahboob, 2016;Tarafdar et al, 2007;Zulfany et al, 2019), unwillingness to extend the use of technology (Fuglseth & Sørebø, 2014), the loss of career promotion (Cooper & Kurland, 2002;Van Steenbergen et al, 2018) and customer dissatisfaction (Christ-Brendemühl & Schaarschmidt, 2020). Moreover, Tarafdar et al (2014) added that there is a potential conflict that could lead to stress due to the use of technology (technostress) among salespeople as many of them would rather spend time interact with consumers than in front of the computer screen (Geiger & Turley, 2006;Rangarajan et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Prior study related to technostress in the workplace shows the association of technostress on organization performances, productivity, satisfaction, career development, health and wellness, attitude toward technology, and job security (Atanasoff & Venable, 2017;Boonjing & Chanvarasuth, 2017;Christ-Brendemühl & Schaarschmidt, 2020;Durucu & Bayraktar, 2020;Fuglseth & Sørebø, 2014;Hung et al, 2015;Mahboob, 2016;Tarafdar et al, 2011;Zulfany et al, 2019). Moreover, in the case of sales professionals, technology use is often seen as an additional stressor that could decrease their overall performance in the sales role (Tarafdar et al, 2014).…”
Section: Technostress In the Workplacementioning
confidence: 99%
“…These extra hours are being spent using communication devices such as email applications and smartphones, many times during odd hours, hitherto private hours. Mahboob and Khan (2016) posit that the use of technology in the workplace through various devices interferes with people's personal time dimension and may lead to stressful work experiences. These interferences with the personal life of employees as a result of technology may completely be beyond the control of employees.…”
Section: Techno-invasionmentioning
confidence: 99%